Design of Real-time Video Transmission System for Drone Reliability. Issue 1 (March 2020) - Guo, Jin; Li, Xiaoyan; Lv, Zhigang; Yang, Yongxia; Li, Liangliang
Abstract: The low-latency reliability video transmission system designed in this paper can complete the functions of real-time image acquisition, transmission and display. The system uses Raspberry Pi 3B+ controller as the core; the 500W pixel camera OV5647 module with CSI interface feature is used as the acquisition module to collect image data in real time and perform compression coding processing; adaptive control of image measurement and control data through 4G public mobile communication network transmission. The experimental results show that the reliability video transmission method designed in this paper can achieve low latency reliability transmission of 480P and 720P resolutions. It can ensure low-latency reception of HD images at the receiving end, and the receiving frame rate is stable above 11FPS, which satisfies the system design requirements.